ChemInform Abstract: Sulfoximine Directed Intermolecular o‐C—H Amidation of Arenes with Sulfonyl Azides. Issue 31 (11th July 2013) - Yadav, M. Ramu; Rit, Raja K.; Sahoo, Akhila K.
Abstract A new Ru(II)‐catalyzed intermolecular ortho‐C—H amidation of various arenes with several sulfonyl azides is reported.